(untitled) (Journal of Advanced Research in Social Sciences, 2019)
New Zealand is considered an egalitarian society, with a progressive policy history in promoting gender equality, however, this paper illustrates how social policy does not always support this agenda. The objective of New Zealand Sole Parent Benefit is to provide temporal financial support to sole parents and their dependents while supporting a transition into formal paid employment. While ultimately aimed at increasing the labour force participation of sole parents, this paper queries to what extent the policy has achieved this objective and why. Recipient statistics are disaggregated by gender to highlight the disproportionate impact on, and unequal outcomes for women. Furthermore, a gendered analysis informed by feminist economists Naileer Kabeer, Diane Elson and Nancy Folbre, alongside statistical evidence of a gender pay gap, occupational segregation and motherhood penalty is applied to demonstrate how market constraints affect New Zealand women’s participation in the labour force, and contribute to the counter intuitive policy results. While these factors do not account for individual differences in motivation, nor individual aspirations, unless the gendered nature of the labour market is addressed, women will continue to face higher rates of engagement on the Sole Parent Benefit and continue to experience disproportionate economic disadvantage and financial insecurity. The consistent use of a gendered analysis in policy design and implementation is essential to reduce gender-based disadvantage, even in countries believed to promote gender equality.